Implementation of Deep Learning Based on the Batobo Tradition to Improve the Cooperative Character of Elementary School Students - Marhadi, Hendri; Erlisnawati; Elmustian; Mardes, Siska; Al Jannah, Raudha Nur Hidayah; Cindy, Vista; Elvina; Hendro, Jhon (International Conference on Elementary Education, 2025)
The character of cooperative is an important aspect that must be possessed by individuals in everyday life. Therefore, the learning carried out should facilitate the development of students' cooperative character. The problem in this study is that students' cooperative character is still relatively low. This study aims to improve students' cooperative character through the implementation of a deep learning approach based on the batobo tradition in science learning for fourth-grade students of SDN 105 Pekanbaru through collaboration with the principles of mindful, meaningful and joyful learning. The batobo tradition is one of the local wisdoms found in the Riau Province community in the agricultural sector that emphasizes cooperative, communication, and shared responsibility. The research method used is a one-group design pretest-posttest experiment with data collection techniques through observation, interviews and documentation. Based on the results of the study, it was found that the implementation of deep learning based on the batobo tradition in science learning can improve the cooperative character of fourth-grade students of SDN 105 Pekanbaru which was previously medium with a percentage of 57,15% increasing to 81,83% with a high category. This can be seen from studentshelping each other complete assignments in groups, being responsible for individual assignments, respecting the opinions of others, sharing with each other, and being open in expressing opinions. It can be concluded that the implementation of deep learning based on the batobo tradition can be used as an innovative learning method to improve the cooperative character of elementary school students.